Gambaran Penyakit Stomatitis Aftosa Rekuren Pasien Klinik Ilmu Penyakit Mulut Rumah Sakit Gigi dan Mulut Universitas Jember - Ayu Mashartini Prihanti; Intan Budi Pramesty; Erna Sulistiyani; Ristya Widi Endah Yani; Hestieyonini Hadnyanawati (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Background: Recurrent Aphthous Stomatitis (RAS) is a common disorder characterized by recurrent ulcers limited to the oral mucosa. The etiology of RAS itself is not yet known for certain, but it is suspected that there are several predisposing factors, including hormonal changes, trauma, malnutrition, stress. Purpose: This study aims to determine the description of RAS in patients at the Oral Medicine Department of Dental Hospital University of Jember based on classification, general condition, suspected predisposing factors, and management. Method: This research is a descriptive observational study with a research population of 722 data from the Department of Oral Medicine, Dental Hospital of University of Jember. The number of samples that met the researchers' criteria was 171. Results: RAS patients is more common in women, 64.91% . RAS occurs in 69.60% of patients aged 21-30 years. RAS were mostly found in patients who did not experience symptoms of systemic factors, in 91.22%. The type of RAS that often occurs is the minor type in 78.37%. 68.42% RAS patients had no suspected predisposing factors. Based on RAS management, pharmacological therapy is divided into two parts, topical pharmacological therapy 59.07% and supportive pharmacological therapy 40.93%. Communication, information and education service was done for all 171 RAS patients. Conclusion: Based on the research conducted, that minor RAS is more prevalent in female 21-30 age group, with absence of underlying diseases, and the most frequently therapeutic modality is topical agents.